Frontiers of Medical Micro/Nanorobotics: in vivo Applications and Commercialization Perspectives Toward Clinical Uses - Soto, Fernando; Chrostowski, Robert (Frontiers in Bioengineering and Biotechnology, 2018)
The field of medical nanorobotics holds considerable promise for advancing medical diagnosis and treatment due to their unique ability to move and perform complex task at small scales. Nevertheless, the grand challenge of the field remains its successful translation towards widespread patient use. We critically address the frontiers of the current methodologies for in-vivo applications and discuss the foreseeable perspectives of their commercialization towards clinical use. We describe the different methodologies from synthetic, chemical to biological nanorobots that have been tested in small mammals as proof of concepts. Moreover, we introduce some examples of emerging patents and commercialization efforts based on nanorobotic technology. We expect to inspire future research efforts in the field of micro/nanorobotics towards future medical diagnosis and treatment.